Synthesis, Spectroscopic and Biological Studies of Some Metal Complexes with 2,3,5,6- O,O,O,O-tetraacetic acid Lascorbic acid - Sultan, J. S.; Mukhlus, A. A.; Musa, F. H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The reaction of L-ascorbic acid with the chloroacetic acid in presence of potassium hydroxide has been investigated. The new product L (2,3,5,6-O,O,O,O-tetraacetic acid L-ascorbic acid) was isolated and characterized by elemental analysis(C.H), 1H, 13C-NMR. Mass spectrum and Fourier transform infrared (FT-IR). The reaction of the ligand (L) (where L = H4L), M+2 = (Co, Ni, Cu, Cd, Pb, Hg, Ca, Mg) has been investigated and was isolated and characterized by FT-IR, UV- visible, conductivity, Atomic absorption and molar ratio (Cd, Co) complexes. Spectroscopic evidence showed that the binding of the M(II) ions are throughy the O-1 Lacton, O-2-OCH2COOH and O-6-OCH2COOH resulting in a six- coordinated metal ion, ï¡, Kf, ï¥max, for Co, Cd complexes, were estimated, ï¢ for Co, Ni, complexes were calculated too. The study of biological activity of the ligand (L) and its complexes (Cu+2, Cd+2, Ca+2) showed various activity toward staphylococcus aureu and Escherichia coli, except Ca- complex didn’t show any effect.